(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Based on BPJS Employment data, the number of work accidents continues to increase until November 2022. It was found that the cause of the high number of work accidents is mostly due to the weakness of the HSE management system implemented by companies that are not carried out continual improvement and are only to meet the level of fulfillment from consumers. The Puri Kelapa Gading North Minahasa Construction Project is a construction project with a high risk of work accidents with the use of labor, heavy equipment and materials on a large scale, so it is necessary to anticipate the potential for accidents and occupational diseases. Therefore, the Socialization of HSE Introduction in the Puri Kelapa Gading Construction Project of North Minahasa was held. This socialization was attended by 25 participants and was carried out using lecture and question and answer methods and distributed pre-test and post-test questionnaires to measure participants’ knowledge. The results of the socialization of HSE recognition increased by 98.4% (Post Test) from 61.2% (Pre Test). The conclusion of the socialization of the introduction of HSE shows that participants realize the importance of applying occupational safety and health when doing construction work.